Study on clinical profile and risk factors associated with pneumonia - Sriram, Gangina; Satyanarayana, Akula (International Journal of Contemporary Pediatrics, 2019)
Background: Modernization, industrialization and urbanization are now posed with the problem of increase in ARI morbidity and mortality. The epidemiological information regarding risk factors and management is scanty. A large gap exists in our knowledge about these factors, which needs to be fulfilled by systematic studies. The present study is designed to identify the risk factors of pneumonia in our area. Methods: This was a prospective clinical study of pneumonia conducted on 94 children who were admitted to Paediatric ward in GSL Medical College General Hospital, Rajahmundry in study duration. Epidemiological factors affecting the same were studied and bronchoscopy was done whenever it was needed. A detailed history of the relevant symptoms, such as fever, cough, rapid breathing, refusal of feeds, noisy breathing, bluish discolouration etc., was collected. Results: The most affected children belonged to the age group of 1 year to 3 years (64.9%). Bronchopneumonia (86.2%) was the most common clinical diagnosis made at admission. According to WHO ARI control programme, 28.7% had pneumonia, 54.3% had severe pneumonia and 17% very severe pneumonia. It was found that younger age group, malnutrition, kutcha house, crowding, poor sanitation facilities, cooking with fuel other than LPG (indoor pollution) and low socio economic status and high respiratory rate were significant risk factors for pneumonia in children. Conclusions: ARI, especially pneumonia is one of the major causes of morbidity and mortality in children. Bronchopneumonia is the predominant form of presentation in infants and preschool children.